Slum Entrepreneurship: A Panacea for Solving Nigeria’s Socio-Economic Hardship in Lagos State, Nigeria - Aladejebi, Olufemi; Bamkole, Peter; Bukola, Amao-Taiwo; Kayode, Agbesuyi (The Journal of Accounting and Management, 2025)
This paper investigates the role of slum entrepreneurship in mitigating socio-economic hardship within selected slum settlements in Lagos State, Nigeria. It explores how the type of entrepreneurial activity, access to capital, social networks, government policy, and entrepreneurial mindset influence business success and poverty alleviation. Prior research on informal entrepreneurship in slums shows mixed results regarding its capacity to foster sustainable economic development, thus necessitating a comprehensive analysis within Lagos’s unique urban context. The study employs a quantitative method approach, with data collected via questionnaires administered to 600 entrepreneurs across six slum areas in Lagos. Descriptive and regression analyses are conducted to examine the relationships between the variables of interest and entrepreneurial outcomes. The findings reveal that formal entrepreneurial activities, adequate access to capital, and robust social networks significantly enhance business sustainability and reduce socio-economic hardship. Conversely, restrictive government policies and limited financial support hinder entrepreneurial growth. Additionally, entrepreneurial motivation and mindset are critical in enabling residents to overcome economic adversity. The study is geographically confined to Lagos State slums, limiting generalizability. However, the findings provide a nuanced understanding of slum entrepreneurship’s multidimensional nature and call for integrated interventions addressing both structural and psychological factors. Policymakers should prioritize formalization incentives, financial inclusion tailored to informal entrepreneurs, community-based support mechanisms, regulatory reforms, and entrepreneurial education programs to maximize slum entrepreneurship’s poverty-alleviation potential. Strengthening entrepreneurship in slums can contribute to reducing urban poverty, improving livelihoods, and fostering inclusive economic growth in rapidly urbanizing African cities. This study advances the literature by combining multiple determinants of entrepreneurial success in slums within a single empirical framework, offering actionable insights for policymakers, practitioners, and scholars focusing on informal urban economies.